UPAYA MENINGKATKAN KETERAMPILAN MENULIS HURUF TEGAK BERSAMBUNG MELALUI PENGGUNAAN ALAT PERAGA SANDPAPER LETTERS BERBASIS MONTESSORI - Fuadi, Diki Najib; Rizal, Soni Samsu; Nur’aeni, Nina (Fakultas Tarbiyah dan Keguruan, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, Ciamis, Jawa Barat, Indonesia, 2019)
This class action research article successfully revealed several findings: First, the ability of teachers to prepare lesson plans for cycle 1 meetings with an average of 88.57, cycle I meetings with an average of 90.57, cycle II meetings with an average of 91.84 and cycle II meeting 2 averages 92.84. Second, the learning process in the first cycle of meeting 1 averaged 88.8, the first cycle of meeting 2 averaged 89.72, the second cycle meeting 1 averaged 91.72 and the second cycle meeting 2 averaged 92.81. Third, the ability to write vertically continued students experience improvement, it can be seen from the results of tests that obtained grades in the first cycle 1 meeting an average of 75.2, the first cycle meeting 2 an average of 77, second cycle meeting 1 an average value of 79, 5 and cycle II meeting 2 an average value of 82. Based on the results of the study it can be concluded that the use of Montessori-based sandpaper letters props on Indonesian subjects the subject of upright writing can improve students' writing skills.